An autocatalytic multicomponent DNAzyme nanomachine for tumor-specific photothermal therapy sensitization in pancreatic cancer - Yan, Jiaqi; Ma, Xiaodong; Liang, Danna; Ran, Meixin; Zheng, Dongdong; Chen, Xiaodong; Zhou, Shichong; Sun, Weijian; Shen, Xian; Zhang, Hongbo (Nature communications, 2023)
Multicomponent deoxyribozymes (MNAzymes) have great potential in gene therapy, but their ability to recognize disease tissue and further achieve synergistic gene regulation has rarely been studied. Herein, Arginylglycylaspartic acid (RGD)-modified Distearyl acylphosphatidyl ethanolamine (DSPE)-polyethylene glycol (PEG) (DSPE-PEG-RGD) micelle is prepared with a DSPE hydrophobic core to load the photothermal therapy (PTT) dye IR780 and the calcium efflux pump inhibitor curcumin. Then, the MNAzyme is distributed into the hydrophilic PEG layer and sealed with calcium phosphate through biomineralization. Moreover, RGD is attached to the outer tail of PEG for tumor targeting. The constructed nanomachine can release MNAzyme and the cofactor Ca 2+ under acidic conditions and self-assemble into an active mode to cleave heat shock protein (HSP) mRNA by consuming the oncogene miRNA-21. Silencing miRNA-21 enhances the expression of the tumor suppressor gene PTEN, leading to PTT sensitization. Meanwhile, curcumin maintains high intracellular Ca 2+ to further suppress HSP-chaperone ATP by disrupting mitochondrial Ca 2+ homeostasis. Therefore, pancreatic cancer is triple-sensitized to IR780-mediated PTT. The in vitro and in vivo results show that the MNAzyme-based nanomachine can strongly regulate HSP and PTEN expression and lead to significant pancreatic tumor inhibition under laser irradiation. Despite delivering gene-specific silencing, the use of deoxyribozymes (DNAzymes) for cancer therapy is limited by toxicity due to off-target effects. Here, the authors develop a multi-component DNAzyme, targeting both miRNA21 and HSP70, to induce tumour-specific sensitisation to photothermal therapy in preclinical models of pancreatic cancer.